The relationship between temperature variables and fruit maturity of 'Granny Smith' apples in the Elgin area - Van Rensburg, Karin L.(Karin Linda) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1995.